Pemanfaatan Artificial Intelligence sebagai Sistem Pendukung Keputusan Berbasis Informasi di Badan Perencanaan Pembangunan Daerah (BAPPEDA) Provinsi Sumatera Barat - Lathifah Octhaviony; Nurizzati Nurizzati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to examine the utilization of Artificial Intelligence (AI) as an information-based decision support system at the Regional Development Planning Agency (BAPPEDA) of West Sumatra Province. This research employed a quantitative descriptive method using a total sampling technique, in which all 48 employees were included as research respondents. Data were collected through a questionnaire using a 4-point Likert scale that had been tested for validity and reliability. Data analysis was conducted using descriptive statistical techniques, including mean, grand mean, and confidence interval calculations. The results indicate that the utilization of AI is categorized as high, with an average score of 3.27. Based on Herbert A. Simon’s Decision Support System model, the indicators of intelligence, design, and choice fall into the good category. Meanwhile, based on the Big Six information literacy model, employees’ ability to manage information is also categorized as good, with an average score of 3.34. These findings suggest that ChatGPT, as part of AI, is capable of assisting employees in processing information, preparing documents, and supporting decision-making more effectively and efficiently. However, the use of ChatGPT also presents a potential dependency risk that may affect employees’ critical thinking skills if not accompanied by proper verification and independent analysis. Therefore, the use of AI should be conducted wisely by considering ethical aspects, accuracy, and the development of human resource competencies.